2015
DOI: 10.1002/chem.201502832
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Response Fluorescent Probe Reveals the H2O2‐Induced H2S Biogenesis through a Cystathionine β‐Synthase Pathway

Abstract: The two signaling molecules H2 S and H2 O2 play key roles in maintaining intracellular redox homeostasis. The biological relationship between H2 O2 and H2 S remains largely unknown in redox biology. In this study, we rationally designed and synthesized single- and dual-response fluorescent probes for detecting both H2 O2 and H2 S in living cells. The dual-response probe was shown to be capable of mono- and dual-detection of H2 O2 and H2 S selectively and sensitively. Detailed bioimaging studies based on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Next, cells were treated with l ‐Cys followed by incubation with 2 , and a strong fluorescence was observed in the Cys‐stimulated HEK293 cells (Figure a). As our study revealed sparfloxacin to be a potent CBS inhibitor, bioimaging of its inhibitory effect was further tested in l ‐Cys‐stimulated HEK293 cells, considering that H 2 S can be produced from l ‐Cys in HEK293 cells via the CBS pathway . The results showed the suppression of l ‐Cys‐induced H 2 S production by sparfloxacin (Figure 6 a, b), implying that sparfloxacin could inhibit endogenous H 2 S biosynthesis.…”
Section: Figurementioning
confidence: 86%
“…Next, cells were treated with l ‐Cys followed by incubation with 2 , and a strong fluorescence was observed in the Cys‐stimulated HEK293 cells (Figure a). As our study revealed sparfloxacin to be a potent CBS inhibitor, bioimaging of its inhibitory effect was further tested in l ‐Cys‐stimulated HEK293 cells, considering that H 2 S can be produced from l ‐Cys in HEK293 cells via the CBS pathway . The results showed the suppression of l ‐Cys‐induced H 2 S production by sparfloxacin (Figure 6 a, b), implying that sparfloxacin could inhibit endogenous H 2 S biosynthesis.…”
Section: Figurementioning
confidence: 86%
“…To further demonstrate the biological applicability of the NBD‐based probes, we examined whether they can detect H 2 O 2 ‐induced H 2 S in living cells. In our previous work, the first H 2 O 2 –H 2 S dual‐response probe was prepared for visualization of H 2 O 2 ‐induced H 2 S in living cells for the first time . Here, when cells were treated with different concentrations of H 2 O 2 followed by 1 , fluorescent signals were observed (Figure , Figure S10).…”
Section: Resultsmentioning
confidence: 97%
“…Changes of the endogenous H 2 S level in living cells by inhibitors AOAA or siRNA were further performed by the gene-knockdown-based fluorescence imaging strategy from our previous work. 11d,23 Normal cells and specific gene-silencing cells were used for the bioimaging of endogenous H 2 S with probe 1 (Fig. S20†).…”
Section: Resultsmentioning
confidence: 99%